(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2014)
Background: Preemptive analgesia, an evolving clinical concept, involves the introduction of an analgesic regimen before the onset of noxious stimuli, with the goal of preventing sensitization of the nervous system to subsequent stimuli that could amplify pain. Pain is inevitable after any surgery. Surgery offers the most promising setting for preemptive analgesia because the timing of noxious stimuli is known. Materials & Methods: This prospective double blind study included 60 children (30 in each group), undergoing major surgery under general anesthesia. Each patient in the study group (Group II) received pre-emptive analgesia (Local anesthesia, per-rectal diclofenac just prior to surgery, per-rectal paracetamol 2 hours prior to surgery) and regular pattern of postoperative pain intervention with per rectal diclofenac and per rectal or oral paracetamol in different phases of postoperative pain management up to 48 hours. On the other hand, each patient of control group (Group I) received pre-emptive analgesia (Local anesthesia & per-rectal diclofenac) regular pattern of postoperative pain intervention with per-rectal diclofenac in different phases of postoperative pain up to 48 hours. The degree of postoperative pain was assessed by universal pain assessment tools (VAS) at defined intervals. Results: Most children in the study group (Group II) has significantly better postoperative pain control with only mild pain at 4th postoperative hours. It is obvious that less pain in Group-II due to synergistic effect of paracetamol and diclofenac. In the control group (Group I) there was persistence of mild pain throughout the observation period i.e. up to 48 postoperative hours. The breakthrough pain occurred more in latter group, two patients needed rescue analgesia. Whereas no patient experienced breakthrough pain requiring rescue analgesia in study group (Group II). Conclusion: Therefore this study concludes that administrations of multimodal pre-emptive analgesia control pain more effectively in children in view of both the degree of pain control and sustainability of pain free state. DOI: http://dx.doi.org/10.3329/jpsb.v2i2.19545